2019
DOI: 10.1002/jib.555
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities and malt quality of durum wheat used in brewing

Abstract: Durum wheat (Triticum durum Desf.) has potential as an adjunct in brewing given its agronomic, chemical and technological properties. The aim of this work were to identify the cultivable microflora and evaluate the technological quality of the durum wheat variety 'Senatore Cappelli' grown and used by a craft brewery in Sardinia, Italy. The isolated bacterial strains were mainly rhizospheric (Kocuria rizophila, Microbacterium aerolatum and Bacillus pumilus) and associated with the microbiota of wheat (Staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Therefore, worldwide legal limits of mycotoxins have been established (Tables 3 and 4). The contamination of malt by mycotoxigenic fungi and mycotoxins can occur throughout the entire brewer production chain, from the field to the malting and brewing (Bianco et al 2019(Bianco et al , 2018Mastanjević et al 2018). Mycotoxigenic fungal species that belong to the genera Aspergillus spp.…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Therefore, worldwide legal limits of mycotoxins have been established (Tables 3 and 4). The contamination of malt by mycotoxigenic fungi and mycotoxins can occur throughout the entire brewer production chain, from the field to the malting and brewing (Bianco et al 2019(Bianco et al , 2018Mastanjević et al 2018). Mycotoxigenic fungal species that belong to the genera Aspergillus spp.…”
Section: Mycotoxinsmentioning
confidence: 99%
“…From the standpoints of nonmainstream wheat cultivars, Benedetti et al [8], Mayer et al [9], and Marconi et al [10] investigated the availability of hulled wheat, such as einkorn, emmer, and spelt, cultivated in Europe as materials for creating new beer styles. Furthermore, Bianco and Fancello [11] attempted to brew beer using Senatore Cappelli, which is a locally grown Italian durum wheat variety.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of up to 20 Fusarium species might be causing it, each of them having a different mycotoxin production profile: F. graminearum and F. culmorum produce DON, NIV and ZEN, F. avenaceum produces moniliformin (MON) and beauvericin (BEA), F. poae mainly produces NIV, T-2 and HT-2 toxins [ 48 ]. Besides the production of mycotoxins, the species belonging to Fusarium can also produce hydrophobins (that act as surfactants, stabilizing the CO 2 bubbles in beer) and enzymes that decrease the ß-glucans levels in the brewing wort, affecting its viscosity, increasing the rate of soluble nitrogen that can interfere with the fermentation process and changing wort colour [ 49 ]. Habschied et al (2014) [ 50 ] suggested that the infection of F. culmorum in wheat can lead to the increase in fungal proteases and activate the plants’ pathogen-related proteins, which are part of its protective strategy (KI of the infected wheat sample 51% versus 49% in control and fungicide-treated samples).…”
Section: Fusarium Fungi In Brewing Cerealsmentioning
confidence: 99%